Development of Multi-axis Differential Optical Absorption Spectroscopy System and its Application in Measuring Atmospheric NO\(_2\) Volume Mixing Ratio in Hanoi - Trung, Dinh Van; Bui Van, Hai; Nguyen, Thi Thanh Bao; Pham, Dong Bang; Vu, Thi Kim Oanh; Nguyen, Xuan Tu; Phung, Viet Tiep; Pham, Hong Minh; Nguyen, Gia Cuong (Communications in Physics, 2022)
Monitoring the concentration and distribution of nitrogen dioxide NO2 in urban environment is of great interest because of the importance of this gaseous pollutant in affecting air quality. In this paper we present the development of a multi-axis differential optical absorption spectroscopy instrument capable of sensitively detecting NO2. The passive instrument collects the sun light scattered by the air molecules and aerosols in the atmosphere and measures the spectrum using a highly sensitive portable spectrometer. The viewing direction of the instrument is controlled through a motor and can be changed continuously. Data analysis of the measured spectra allows us to simultaneously determine the differential scant column density of NO2 and oxygen dimer O4. From the accurately known concentration of O4, the effective optical path length of scattered sun light near the horizontal direction could be derived, which in turn provides an estimate the concentration of NO2. The measured data show that the concentration of NO2 in Hanoi is in the range 1.5 ppb. We also present the detection of formaldehyde HCHO and possible detection of glyoxal CHOCHO. Our sensitive instrument opens up the possibility to monitor the concentration of other molecular species of interest in urban environment of Hanoi.